Human Resource Development Policy and Leadership Style Effect on Subdistrict Officials Performance with Discipline Mediation - Subiha Subiha; Titin Ruliana; Meiki Permana; Hadi Purnomo (Goodwood Publishing, 2026)
Purpose: This study aims to examine the effect of human resource development policy implementation and leadership style on the performance of subdistrict government officials, with work discipline as a mediating variable in East Kutai Regency. Research Methodology: This study used a quantitative, hypothesis-testing approach with 210 purposively selected government apparatus respondents from East Kutai Regency. Data were collected using structured questionnaires on a five-point Likert scale and analyzed with SmartPLS 3.0 software. Results: The results show that the implementation of human resource development policies does not significant effect on the government apparatus performance, whereas leadership style has a positive and significant effect. Both human resource development policies and leadership style significantly influence work discipline, which in turn positively affects performance. The coefficient of determination (R²) indicated that 54.6% of work discipline and 49.6% of government apparatus performance were explained by the model, suggesting moderate explanatory power. Conclusions: Work discipline mediates the effect of leadership style and human resource development policies on government official performance, while effective leadership and HR policies improve discipline and organizational performance. Limitations: The study is limited to subdistrict government officials in East Kutai Regency and uses a cross sectional design with perception based questionnaire data. Contributions: This research provides empirical evidence on the mediating role of work discipline in public sector performance and offers insights for local government in designing more effective human resource development and leadership strategies.